Role of Technological Institutions in Technology Innovations and their Impacts on National Security - Sharma, P. B. (Journal of Engineering Education Transformations, 2006)
In the era of Knowledge intensive work environment, it is important to establish Knowledge Infrastructure in engineering institutions to foster technology innovations and technology incubation. The students of engineering in India are a reservoir of ta lent and have high innovative and creative abilities. The establishment of knowledge infrastructure shall unleash technology innovations in institutions of higher learning and shall help accelerate the growth of student companies thus, creating an enabling environment for techno-entrepreneurship. Technology innovations have a direct impact on ensuring national security. The paper outlines the focus areas of technology innovation which could be taken up in engineering institutions in India.